The Effectiveness of the Responsive Teaching Parent-mediated Developmental Intervention Programme in Turkey: A pilot study - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2011)
The case study was conducted to examine the feasibility of an early intervention curriculum called Responsive Teaching with two five-year-old children from Turkey who had significant developmental delays. This study determined whether Turkish mothers might be successful in learning to become more responsive to their children, and whether this would result in significant improvements in their children's development. Both dyads received 28 individual parent-child intervention sessions which were conducted over a four-month period of time. Pre-, mid-, and post-assessments indicated improvements in the mothers' responsiveness to their children and the children's levels of engagement with their parents. There were also improvements in the children's language and personal social development. Mothers reported that Responsive Teaching helped them learn to interact more effectively with their children and that this resulted in longer and more enjoyable interactions with them. Results from this investigation are discussed in terms of their implications for providing developmental services to preschool-aged children with disabilities in Turkey.
Keywords: developmental disability; developmental intervention; early intervention; parent-child interaction; pilot study; Responsive Teaching Programme; Turkish children; Turkish mothers; MATERNAL RESPONSIVENESS; DISABILITIES; TEMPERAMENT; ATTACHMENT; LANGUAGE; CHILDREN; INFANTS